Deterministic fabrication of 3D/2D perovskite bilayer stacks for durable and efficient solar cells - Sidhik, Siraj; Wang, Yafei; De Siena, Michael; Asadpour, Reza; Torma, Andrew J.; Terlier, Tanguy; Ho, Kevin; Li, Wenbin; Puthirath, Anand B.; Shuai, Xinting; Agrawal, Ayush; Traore, Boubacar; et al. (Science (American Association for the Advancement of Science), 2022)
Realizing solution-processed heterostructures is a long-enduring challenge in halide perovskites because of solvent incompatibilities that disrupt the underlying layer. By leveraging the solvent dielectric constant and Gutmann donor number, we could grow phase-pure two-dimensional (2D) halide perovskite stacks of the desired composition, thickness, and bandgap onto 3D perovskites without dissolving the underlying substrate. Characterization reveals a 3D–2D transition region of 20 nanometers mainly determined by the roughness of the bottom 3D layer. Thickness dependence of the 2D perovskite layer reveals the anticipated trends for n-i-p and p-i-n architectures, which is consistent with band alignment and carrier transport limits for 2D perovskites. We measured a photovoltaic efficiency of 24.5%, with exceptional stability of T 99 (time required to preserve 99% of initial photovoltaic efficiency) of >2000 hours, implying that the 3D/2D bilayer inherits the intrinsic durability of 2D perovskite without compromising efficiency. Two-dimensional (2D) halide perovskite passivation layers grown on three-dimensional (3D) perovskite can boost the power conversion efficiency (PCE) of solar cells, but spin-coating of these layers usually forms heterogeneous 2D phases or only ultrathin layers. Sidhik et al . found that solvents with the appropriate dielectric constant and donor strength could grow phase-pure 2D phases of controlled thickness and composition on 3D substrates without dissolving them. Solar cells maintained a peak PCE of 24.5% for 2000 hours with less than 1% degradation under continuous light at 55°C and 65% relative humidity. —PDS Solvents enable growth of phase-pure two-dimensional perovskites without dissolving three-dimensional perovskite substrates.